Effect Of The Contact Time Of Candlenut Shell Charcoal And H3PO4 Activator As On The Purification Process Of Used Cooking Oil - Yustina Bapa; Loth Botahala (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Research on Comparison of the Contact Time of Candlenut Charcoal with H3PO4 Activator in the Process of Purifying Used Cooking Oil has been conducted. The purpose of this study was to determine the ability of candlenut shells activated with H3PO4 against purifying used cooking oil. The variation of the number of candlenut shells used is 1 gram, 2 grams, and 3 grams and the variation of contact time is 10 minutes, 30 minutes and 60 minutes. The results showed that the activation of hazelnut shell using H3PO4 fulfills SNI 16-3730-1995, while the results of used cooking oil purification with 2 grams of activated charcoal in 60 minutes resulted in a decrease in peroxide number of 64.58% and free fatty acids of 54, 84%.